Peran Guru Kelas Dalam Menumbuhkan Nilai-Nilai Karakter Jujur Siswa di Madrasah Ibtidaiyah - Maulidia, Wafiqoh; Astuti, Mardiah; Fatimah, Siti; Handayani, Tutut; Boty, Middya (Universitas Islam Negeri Raden Fatah Palembang, 2024)
The commendable morals exemplified by the Prophet Muhammad SAW. as a human example through one of his characteristics, namely honesty. However, the world of education is currently starting to experience decadence in morals. Dishonesty stems from things like cheating and lying. Class teachers play a role in the formation of students personalities. Therefore, honest character must be instilled as early as possible in elementary students so that it becomes a provision for life in society. This research aims to describe role of class teachers in cultivating students honest character values along with supporting and inhibiting factors. The type of research used is descriptive qualitative. Data was collected using observation, interviews, and documentation methods. The results of this research indicate that the role of class teachers in cultivating students honest character is the role of teachers as teachers, role models, educators, mentors and motivators. Supporting factors for class teachers in cultivating students honest character values are habituation at school, communication between teachers and parents, and involvement of the school. Meanwhile, the inhibiting factors are family, peers, and students self-awareness. This research emphasises the importance of the classroom teacher's role in teaching honesty to students to shape moral and ethical character. Teachers are expected to be teachers, role models and motivators who create an environment that supports honesty. Suggested follow-up actions include increasing cooperation between schools, parents and communities to build a sustainable culture of honesty, as well as providing training for teachers in effective teaching methods. The research also encourages further study of inhibiting factors related to the role of family and social interaction among peers.